Determination of Optimum Level of Seeding Rate of Silver Leaf Desmodim Intercropping with Desho Grass for Dry Matter Yield and Yield-Related Components in Western Ethiopia - Wakgari Keba (Advances in Agriculture)
Compatible production of forage grasses and legumes through intercropping is one of the best options to achieve higher biomass yield and forage quality for animal production in areas where land and other resources are scarce. This study was conducted in 2017 and 2018 with the aim of evaluating the best-match level of seeding rate of silverleaf desmodium (SLD) intercropped with desho grass (Pennisetum pedicellatum) in a randomized complete block design with three replications. The treatment consists of three levels of seeding rate of SLD (2, 4, and 6 kg ha−1) and one pure plot of each species. The result of this study showed that the intercropping of 6 kg ha−1 SLD with 100% of desho’s recommended plant population (50,000 plants ha−1) produced the highest forage dry matter yield and maximum plant height. The total dry matter yield (TDMY) of the intercrops was also significantly varied for the tested treatments. Accordingly, 6 kg ha−1 of SLD intercropped with 100% recommended seed rate of desho ha−1 gave the highest forage TDMY, which surpasses both the grass and legume yields in monoculture. The total land equivalent ratio (LER), which shows system productivity, was also different among the treatments. About 6 kg ha−1 of SLD intercropped with 100% recommended seed rate of desho also produced the highest LER (1.51). Thus, in Bako and similar agro-climatic conditions, where arable land is heavily covered with food crops, desho grass intercropping with SLD can be used as one of the best strategic options for producing feeds of energy and protein sources simultaneously on the same area of land.